Lymphocytoma Cutis - Gangopadhyay DN; Dey S K; Barbhuiya J N (Wolters Kluwer Medknow Publications, 1999)
Lymphocytoma cutis, a type of pseudolymphoma, is a rare disorder with distinct clinical and histopathological features. A female patient presented with an asymptomatic, indolent dull erythematous, slowly progressive, firm nodular lesion of more than five years duration on right side of face diagnosed histopathologically as lymphocytoma cutis. The lesion showed no tendency to self- healing in more than five years duration and did not respond to chloroquin or to systemic and topical steroids.